Multilayered regulation of iron homeostasis in Arabidopsis - Spielmann, Julien; Fanara, Steven; Cotelle, Valérie; Vert, Grégory (Frontiers in Plant Science, 2023)
Iron (Fe) is an essential micronutrient for plant growth and development due to its role in crucial processes such as photosynthesis and modulation of the redox state as an electron donor. While Fe is one of the five most abundant metals in the Earth's crust, it is poorly accessible to plants in alkaline soils due to the formation of insoluble complexes. To limit Fe deficiency symptoms, plant have developed a highly sophisticated regulation network including Fe sensing, transcriptional regulation of Fe-deficiency responsive genes, and post-translational modifications of Fe transporters. In this mini-review, we detail how plants perceive intracellular Fe status and how they regulate transporters involved in Fe uptake through a complex cascade of transcription factors. We also describe the current knowledge about intracellular trafficking, including secretion to the plasma membrane, endocytosis, recycling, and degradation of the two main Fe transporters, IRON-REGULATED TRANSPORTER 1 (IRT1) and NATURAL RESISTANCE ASSOCIATED MACROPHAGE PROTEIN 1 (NRAMP1). Regulation of these transporters by their non-Fe substrates is discussed in relation to their functional role to avoid accumulation of these toxic metals during Fe limitation.